2000
DOI: 10.1093/humrep/15.12.2591
|View full text |Cite
|
Sign up to set email alerts
|

Zygote evaluation: an efficient tool for embryo selection

Abstract: One of the main problems concerning IVF units is the need to decrease the occurrence of multiple pregnancies in their practice without affecting the overall success rate. Different embryological parameters concerning every step of the early embryo development are known to have some predictive value for implantation potential. In this prospective study, a pronuclear scoring system was used to classify zygotes into six patterns from 0 to 5. Cleaved, day 3 embryos developed from pattern 0 zygotes, which was descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 32 publications
1
36
0
8
Order By: Relevance
“…This is usually achieved either by the extended culture of human embryos to the blastocyst stage [5,6] or by the morphological analysis and selection of the highest quality embryos for transfer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More recently, the assessment of zygote quality has been applied [23][24][25][26][27][28][29][30][31][32]. Although these techniques have greatly assisted in achieving an acceptable pregnancy rate with the minimum number of embryos transferred into the uterus, one aspect of these protocols is that non-transferred embryos are discarded or cryopreserved.…”
Section: Introductionmentioning
confidence: 99%
“…This is usually achieved either by the extended culture of human embryos to the blastocyst stage [5,6] or by the morphological analysis and selection of the highest quality embryos for transfer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More recently, the assessment of zygote quality has been applied [23][24][25][26][27][28][29][30][31][32]. Although these techniques have greatly assisted in achieving an acceptable pregnancy rate with the minimum number of embryos transferred into the uterus, one aspect of these protocols is that non-transferred embryos are discarded or cryopreserved.…”
Section: Introductionmentioning
confidence: 99%
“…Several oocyte, zygote, and cleavage-stage grading methods that were not used in this study have been shown to correlate with an embryo's implantation potential (1)(2)(3)(5)(6)(7)11,12,28,(30)(31)(32)(33)(34)(35)(36)(37). Tesarik et al (1) showed that the relationship between the number of embryos transferred and the multiple rate depended on PN-S morphology; transfer of 2 embryos from pattern zero zygotes usually resulted in a twin pregnancy.…”
Section: Discussionmentioning
confidence: 76%
“…Embryos with certain pronuclear-stage (PN-S) features, such as the presence of a halo and alignment of nucleoli within the PN, have better day-3 to day-6 cleavage rates and morphology and also implant at higher rates than embryos from zygotes lacking these features (1)(2)(3)(4)(5)(6)(7). Zygotes cryopreserved at the PN-S have high rates of cryosurvival and result in high pregnancy rates after post-thaw culture to the 4-to 6-cell stage (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, these morphological features have been chosen as a quality indicator of the fertilized oocyte. In fact, it has been described that a minimum number of NPB in each PN, and the same distribution in the two PNs, have both been positively correlated with pregnancy [14][15][16]. In addition, zygotes presenting polarised NPB appear to have a better implantation potential [12,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors have reported different results regarding the prognostic value of each PN feature. Some studies have reported a strong association between the PN orientation [9][10][11] or the number and distribution of NPB [12][13][14][15][16] and the implantation potential; others have suggested that an increased chance of implantation exists when the cytoplasmic halo is present in zygotes [2,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%